Piracy in a two-sided software market - Alexander Rasch; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This paper studies the impact of software piracy in a two-sidedmarket setting. Software platforms attract developers and users to maximize their profits. The equilibrium price structure is affected by piracy: license fees to developers are higher with more software protection but the impact on user prices is ambiguous. A conflict between platforms and software developers over software protection may arise: whereas one side benefits from better protection, the other party loses out. Under platform compatibility, this conflict is no longer present.
Keywords: L11; L86; 330; developer; piracy; platform; software; two-sided markets